2012
DOI: 10.1016/j.clinbiochem.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Performance of succinylacetone assays and their associated proficiency testing outcomes

Abstract: Background-Succinylacetone (SUAC) is the primary metabolic marker for hepatorenal tyrosinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…Precision (the ability to consistently reproduce a result when sub-samples are taken from the same specimen) results were presented in seven studies with inter-assay coefficients of variation (CV) at different SUAC concentrations of 10.0-12.2% [ 14 ], 7.1-8.5% [ 21 ], 3.50-4.49% [ 22 ], 5.8-13% [ 19 ], 15.8-16.7% [ 24 ], 17.29-19.00% [ 23 ] and 30% in a pooled sample assay [ 20 ]. Taken together, the analytical performance of the screening tests used in the included studies was in agreement with previously reported proficiency testing outcomes [ 26 , 28 , 29 ], showing large between-laboratory differences in SUAC recoveries (mostly incomplete recoveries) depending on the method used and reproducible within-laboratory recoveries. There is need to harmonise quantitative results among laboratories.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Precision (the ability to consistently reproduce a result when sub-samples are taken from the same specimen) results were presented in seven studies with inter-assay coefficients of variation (CV) at different SUAC concentrations of 10.0-12.2% [ 14 ], 7.1-8.5% [ 21 ], 3.50-4.49% [ 22 ], 5.8-13% [ 19 ], 15.8-16.7% [ 24 ], 17.29-19.00% [ 23 ] and 30% in a pooled sample assay [ 20 ]. Taken together, the analytical performance of the screening tests used in the included studies was in agreement with previously reported proficiency testing outcomes [ 26 , 28 , 29 ], showing large between-laboratory differences in SUAC recoveries (mostly incomplete recoveries) depending on the method used and reproducible within-laboratory recoveries. There is need to harmonise quantitative results among laboratories.…”
Section: Discussionsupporting
confidence: 88%
“…For example, the SUAC cut-offs used in the screening test to identify possible cases of TYR1 ranged from 1.29 μmol/l [ 23 ] to 10 μmol/l [ 19 ]. Proficiency testing results for SUAC in dried blood spots have shown large differences among screening laboratories in SUAC recovery reflecting analytic biases, which might explain the wide variation in cut-off values of the studies in our review [ 26 ]. Differences in recovery could be explained by the method used (kit TMS vs. non-kit TMS; butyl ester derivatisation vs. non-derivatisation), DBS extraction strategy (freshly punched DBS, residual DBS or co-extraction of AA, AC, and SUAC, respectively), internal standard used ( 13 C-SUAC, 5,7-dioxooctanoic acid, or TMS kit internal standard), or the calibration strategy used (DBS calibrators, TMS internal standard/other liquid standard or kit internal standard only, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SUAC was added to the program in 2008 in response to an increasing number of state public laboratories adopting SUAC testing in their panels [25, 26]. The PT program distributes quarterly panels of blind-coded DBS specimens to participating laboratories and provides an independent external assessment of each laboratory’s performance.…”
Section: Methodsmentioning
confidence: 99%
“…It is a qualitative test with less than 4 hours procedure. In our study the sensitivity of the test was higher than 95%, which is completely acceptable for being a screening test ( 13 ).…”
Section: Discussionmentioning
confidence: 47%